Cardiac stem cell genetic engineering using the ααMHC promoter. (November 2009) - Bailey, Brandi; Izarra, Alberto; Alvarez, Roberto; Fischer, Kimberlee M; Cottage, Christopher T; Quijada, Pearl; Dííez-Juan, Antonio; Sussman, Mark A
Aims: Cardiac stem cells (CSCs) show potential as a cellular therapeutic approach to blunt tissue damage and facilitate reparative and regenerative processes after myocardial infarction. Despite multiple published reports of improvement, functional benefits remain modest using normal stem cells delivered by adoptive transfer into damaged myocardium. The goal of this study is to enhance survival and proliferation of CSCs that have undergone lineage commitment in early phases as evidenced by expression of proteins driven by the αα-myosin heavy chain (ααMHC) promoter. The early increased expression of survival kinases augments expansion of the cardiogenic CSC pool and subsequent daughter progeny.Materials & methods: Normal CSCs engineered with fluorescent reporter protein constructs under control of the ααMHC promoter show transgene protein expression, confirming activity of the promoter in CSCs. Cultured CSCs from both nontransgenic and cardiac-specific transgenic mice expressing survival kinases driven by the ααMHC promoter were analyzed to characterize transgene expression following treatments to promote differentiation in culture.Results & conclusion: Therapeutic genes controlled by the ααMHC promoter can be engineered into and expressed in CSCs and cardiomyocyte progeny with the goal of improving the efficacy of cardiac stem cell therapy.